Benign Nerve Sheath Myxoma in an Infant Misdiagnosed as Infantile Digital Fibromatosis. Issue 4 (16th May 2016) - Güngör, Şule; Şişman, Servet; Kocaturk, Emek; Oguz Topal, Ilteris; Yıldırım, Selda
Abstract: Herein we present the case of a 16‐month boy, clinically diagnosed with infantile digital fibromatosis, but 9 months after continued growth, the mass was excised and the histopathologic diagnosis was that of a benign nerve sheath myxoma. We present this case to emphasize that nerve sheath myxomas (also known as myxoid neurothekeoma) should be included in the differential diagnosis of dermal nodules in infants.